Byłaś moim niebem…, czyli o miłości, która nie umiera - Karkut, Dorota (Dydaktyka Polonistyczna, 2017)
In the review a book of Barbara Litwicka You were my heaven was discussed. Issues brought up by the author are providing readers with not only the entertainment and the relaxation, but above all provoking reflection. They are determining the axiological and existential perspective, encouraging to empathic reading. This is one of the books which through the composition, genre and creations of the main characters open up various interpretative proposals, associations and discussions.